Nonreciprocal propagation in a non-Hermitian silicon photonic coupler employing graphene saturable absorption - Chatzidimitriou, Dimitrios; Pitilakis, Alexandros; Yioultsis, Traianos; Kriezis, Emmanouil (EPJ Web of conferences, 2020)
We present the concept, analysis and design of a nonreciprocal system of coupled nonlinear waveguides, operating at the near infrared. We exploit the spatial asymmetry induced by the exceptional points of a non-Hermitian coupler which, combined with saturable absorption in the nonlinear regime, can break Lorentz reciprocity. In this work, we introduce asymmetric losses in a pair of coupled silicon waveguides by overlaying only one of them with unbiased graphene, subject to saturable absorption. The device can be used as a broadband half-duplex isolator: a two-port component offering unidirectional transmission of high-power signals.